التأمين كألية لإدارة المخاطر في الجزائر( 2000-2013) - حمزة بالي . منور أوسرير . (جامعة الوادي - University of Eloued, 2015)
تعتبر مواجهة الأخطار من أكبر التحديات التي تواجه المؤسسات، فإذا كان البقاء والاستمرار والربحية تمثل أهدافا رئيسية لأي مؤسسة اقتصادية، فتسيير ومعالجة الأخطار والتكيف مع البيئة تمثل الشروط الضرورية لتحقيق هذه الأهداف. كلنا يدرك أننا في عصر تحيطه الأخطار من كل مكان، ولاسيما أننا نتعامل مع تكنولوجيا معقدة، ولا ندري في أي لحظة تنقض علينا الأخطار التي قد لا نقوى على مواجهتها، لذا فإن استدراك الأخطار والتحكم بها هو طريق الأمان المنشود، يعتبر التأمين في هذا المجال من أفضل الوسائل لإدارة الأخطار، بحيث يتأتى من خلال هذا النظام نقل عبء الخطر من الوحدة الإنتاجية إلى شركة التأمين والتي بدورها تتحمل تغطية الخسائر لكافة العناصر المؤمن عليها لقاء قسط التأمين الذي يدفعه صاحب القرار لقاء الأمان The fact of facing risks is considered as one of the important challenges for the institutions. For any economic firm the management and the treatment of the risks, as well as, the adaptation within the environment are the necessary conditions to acheive the main targets which are: firm survival, Firm continuity, firm profitability. Nowadays, despite of the surrounding risks' awareness and the dealing with complex technology we don't know the moment of danger which we have not the ability to face it, so the risks' identification and control is the desirable safety way. Insurances in this regards is the most efficient way for risks' management. Such process will transfer the risks' burden from the production unit to the insurances companies which in turn cover all the losses of the all assured elements against to the insurance premium " paid by the decision-maker against insurance".
مقال
Keywords: إدارة الخطر, التأمين، شركات التأمين.; risk management , the assurance, insurances companies